The impact of the COVID-19 pandemic on the profile of interstitial lung disease presenting to the pulmonary medicine department of a tertiary care center in western India - Unnati Desai; Ketaki Utpat; Aravind Raj (Monaldi Archives for Chest Disease)
The COVID-19 pandemic impacted the etiological pattern of interstitial lung diseases (ILDs). This study aimed to analyze the profile of ILDs presenting to our department during the pandemic. Specifically, this cross-sectional observational study was conducted with the institute's ethics committee approval in the year 2021-2022. The clinical profile and history of COVID-19 illness in ILDs were noted. Data was analyzed in percentages and means. Of the 136 cases included, 85 (62.5%) were men and 51 (37.5%) women. The average age was 55.1±12.01 years. Cough and breathlessness were the predominant symptoms. A total of 20 (15%) participants gave a past history of COVID-19, of whom 2 (10%) had mild, 2 (10%) had moderate, and 16 (80%) had severe COVID-19 illness. Among them, 9 (45%) cases had pre-existing ILD. Thus, 11 (55%) had new-onset ILD attributed to severe COVID-19. This contributed to 8% of the ILD caseload. Predominant ILD patterns on high-resolution computed tomography thorax were usual interstitial pneumonia, hypersensitivity pneumonitis (HP), and non-specific interstitial pneumonia. The ILD diagnosis with multidisciplinary discussion was idiopathic interstitial pneumonitis in 44 cases, HP in 36, connective tissue disease-ILD in 35, post-COVID-19 ILD in 11, sarcoidosis in 8, and silicosis in 2. COVID-19 was attributed to only 8% of the caseload and was the fourth most common cause of ILD. Generally, ILD cases were younger patients and had severe disease.